Phytochemical investigation and antimicrobial assessment of Bellis sylvestris leaves. (September 2016) - Scognamiglio, Monica; Buommino, Elisabetta; Coretti, Lorena; Graziani, Vittoria; Russo, Rosita; Caputo, Pina; Donnarumma, Giovanna; D'Abrosca, Brigida; Fiorentino, Antonio
Graphical abstract: Highlights: A phytochemical study on Bellis sylvestris was carried out. Twenty eight secondary metabolites belonging to different classes were isolated. Three compounds were reported for the first time. Isolated compounds have been evaluated for their antimicrobial activity. Abstract: The phytochemical study of Bellis sylvestris has been carried out. This study led to the isolation of 28 secondary metabolites belonging to different classes. The structures of these compounds have been elucidated on the basis of extensive 2D-NMR spectroscopic analyses, including COSY, TOCSY, HSQC, CIGAR-HMBC, H2BC and HSQC-TOCSY, along with Q-TOF HRMS 2 analysis. Three of them, two megastimane derivatives and a glycoside of 3-hydroxy-1-(4-hydroxy-3, 5-dimethoxyphenyl)-1-propanone, were reported for the first time. The compounds isolated from Bellis sylvestris were tested for their antimicrobial activity against some microorganisms associated with urinary tract infections ( Proteus mirabilis, Pseudomonas aeruginosa, Streptococcus aureus and Candida albicans ). The bacterial strains showed variable degrees of susceptibility to the compounds. Selected compounds were evaluated for their anti-biofilm properties against Pseudomonas aeruginosa and Candida albicans . Caffeic and rosmarinic acids were the once showing a higher reduction rate of biofilm formation.